2010
DOI: 10.1007/s11033-010-0196-x
|View full text |Cite
|
Sign up to set email alerts
|

l-Dopa decarboxylase expression profile in human cancer cells

Abstract: L-Dopa decarboxylase (DDC) catalyses the decarboxylation of L-Dopa. It has been shown that the DDC gene undergoes alternative splicing within its 5'-untranslated region (UTR), in a tissue-specific manner, generating identical protein products. The employment of two alternative 5'UTRs is thought to be responsible for tissue-specific expression of the human DDC mRNA. In this study, we focused on the investigation of the nature of the mRNA expression in human cell lines of neural and non-neural origin. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
3
0
11
Order By: Relevance
“…1: Panel c). Our work has also shown that HTB-14 cells are inactive towards the decarboxylation of L-Dopa, although they express the enzyme [14]. These data, along with the Triton X-114 separation results, argue against the possibility that the detected membrane-associated molecules are derived from the unspecific attachment of the soluble enzyme with membrane fraction and is in good agreement with the results of Kuhn et al [34] who reported the absence of TH in the aqueous phase in granule membranes after fractionation with Triton X-114.…”
Section: Temperature-induced Phase Separation Of Proteins In Triton Xsupporting
confidence: 64%
“…1: Panel c). Our work has also shown that HTB-14 cells are inactive towards the decarboxylation of L-Dopa, although they express the enzyme [14]. These data, along with the Triton X-114 separation results, argue against the possibility that the detected membrane-associated molecules are derived from the unspecific attachment of the soluble enzyme with membrane fraction and is in good agreement with the results of Kuhn et al [34] who reported the absence of TH in the aqueous phase in granule membranes after fractionation with Triton X-114.…”
Section: Temperature-induced Phase Separation Of Proteins In Triton Xsupporting
confidence: 64%
“…Alternative promoter usage, combined with alternative splicing within the 5′-untranslated region (5′ UTR), gives rise to two different mRNA transcripts, designated neuronal and non-neuronal, but the proteins encoded by these mRNAs are identical [27,28,29,30]. The neuronal type transcript has also been detected in non-neuronal human tissues, such as placenta, kidney, and leukocytes [28,31,32,33] and, more recently, in liver cells [21]. Alternative splicing events have also been reported within the coding region of the gene [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…These protein isoforms might participate in metabolic processes having alternative functions (Adamopoulos et al, 2019). For example, HeLa and HTB14 (human glioblastoma) coexpress the non-neural full-length DDC mRNA and the alternative neural transcript lacking exon 3, but no enzymatic activity is detectable in the cellular extracts (Chalatsa et al, 2011). Nevertheless, T98G cells do not seem to express the gene coding DDC (Functional Annotation of the Mammalian Genome, 2012).…”
Section: Discussionmentioning
confidence: 99%